The choice of code in a press conference of Maudy Ayunda as government spokesperson for Indonesia’s G20 presidency. - Nadhatul Nurul Hasanah (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
The purpose of this article is to identify the use of code switching from Maudy Ayunda as the government spokesperson for the G20 presidency. Using descriptive qualitative research methods from the speech of three videos of Maudy Ayunda and use documentation technique to collect the data after that analyze the data used theory from Miles and Huberman (1994:10) the author found that there are 2 forms of code switching used by Maudy Ayunda, namely inter-centential switching and intra-centential switching. The use of code switching is for several reasons, namely because Maudy Ayunda has a good educational background, maudy ayunda studied in America and England some time ago and the second reason is because Maudy Ayunda uses code switching for reasons of lexical need. Therefore, the use of code switching is carried out not only for no reason, but code switching is used for various specific reasons.